INTEGRASI HUKUM ISLAM DAN HUKUM ADAT DALAM PEWARISAN MASYARAKAT BUGIS BONE - Asni Zubair; Muljan Muljan; Rosita Rosita (Institut Agama Islam Negeri Bone, 2020)
AbstractIntegration of Islamic law and customary law of inheritance that run in the Bugis community in District Palakka Bone takes place in the form of assimilation, syncretic, acculturative, and legitimacy. Integration in a syncretic form can be seen in the division of inheritance society that make Islamic law and customary law as a reference. Integration in the form acculturative can be seen at the time of the division of property, there is executed before the death, and there is also carried out after the death of the testator. The integration in the form of legitimacy can be seen from the case of the division of inheritance community continue to provide part of property to the son of the heir who had died earlier than the heir known as substitute heirs. Integration of Islamic law and customary law apply to the division of the community estate Bugis Bone in District Palakka namely because: a. between Islamic law and customary law have interacted for a long time, complementary in addressing the legal needs of the community, b. Islamic law and customary law used as a reference and a major cornerstone in the division of the community estate, c. Islamic law and customary law into the legal awareness of the public to follow both of these rules. d. between Islamic law and customary law have a common vision and goal to bring peace to people's lives.